The Effect of Marijuana Legalization on Jail Populations in Washington State. (September 2020) - Stanton, Duane; Mei, Xiaohan; Kim, Sohee; Willits, Dale; Stohr, Mary; Hemmens, Craig; Wu, Guangzhen; Lu, Ruibin; Makin, David; Lovrich, Nicholas
In 2012, Washington State legalized the production, sale, and possession of marijuana through Initiative 502. Advocates of legalization argued that it would decrease the jail population and reduce the disproportionate incarceration of minorities, reasoning that the police would refocus their resources on other matters. In order to evaluate this assumption, we examined jail booking data using a set of interrupted time-series regression models. Our findings indicate that jail population trends differ among counties across time and with respect to impacts on minorities and women. With regard to ethnic and racial disproportionate impact, there appears to be little positive change.